2021
DOI: 10.3390/ijerph18052693
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic Low Back Pain and Burnout among Hungarian Workers

Abstract: Burnout is an increasingly prevalent syndrome mainly involving those working in human services. Although it is categorized as an occupational phenomenon and not as a medical condition, it seems to be strongly associated with several diseases such as pain syndromes. However, no studies examined the association between neuropathic low back pain and burnout. This questionnaire-based study was carried out between April 2019 and March 2020 in three main sites among teachers, social workers and healthcare workers. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
3
0
6
Order By: Relevance
“…Burnout can have serious mental and physical consequences including mental issues as insomnia or mood disorders and can also be closely associated with cardiovascular complications, chronic pain syndromes and increased sudden mortality in the young (< 45 years), which underlines the importance of proper screening [ 11 14 ]. However, this rate is comparable to the results of our previous Hungarian studies focusing on different population of workers [ 26 , 34 , 35 ]. Similar to healthcare workers, their salaries are far below the Hungarian average and they also tend to being overwhelmed with work, which are the most likely explanations of higher burnout rates in these populations.…”
Section: Discussionsupporting
confidence: 90%
“…Burnout can have serious mental and physical consequences including mental issues as insomnia or mood disorders and can also be closely associated with cardiovascular complications, chronic pain syndromes and increased sudden mortality in the young (< 45 years), which underlines the importance of proper screening [ 11 14 ]. However, this rate is comparable to the results of our previous Hungarian studies focusing on different population of workers [ 26 , 34 , 35 ]. Similar to healthcare workers, their salaries are far below the Hungarian average and they also tend to being overwhelmed with work, which are the most likely explanations of higher burnout rates in these populations.…”
Section: Discussionsupporting
confidence: 90%
“…It may be surprising that, despite the pressure, professional demands or thoughts of the employee being irreplaceable, not absenteeism but presenteeism brings greater adverse economic consequences. In the questionnaire-based cross-sectional study [26], which examined the association between neuropathic pain and burnout, the authors showed that both disorders shared congruous risk factors and effects, which may indicate a similar pathophysiology. Work environment, interpersonal and professional conflicts, and emotional distress leading to emotional depletion, detachment from work and reduced productivity are categorized as factors influencing the appearance of occupational burnout.…”
Section: Functional Impairment In Occupational Lifementioning
confidence: 99%
“…It is usually developed in response to poor working circumstances, interpersonal interactions, poor work management, and administration (Moueleu Ngalagou et al, 2019;Ndongo et al, 2020;Civilotti et al, 2021;Goldstein and Alesbury, 2021;Losung et al, 2021;Sener et al, 2021;Wirkus et al, 2021). It usually affects medical professionals, teachers, police officers, army soldiers, as well as many other professionals (Burki, 2020;Ndongo et al, 2020;Goldstein and Alesbury, 2021;Grupe et al, 2021;Llorca-Pellicer et al, 2021;Mák et al, 2021;Márquez et al, 2021;Ribeiro et al, 2021;Righi et al, 2021;Wirkus et al, 2021). The syndrome is characterized by various symptoms ranging from emotional to psychiatric, cognitive, and psychosomatic symptoms with different severities (Bauer et al, 2006;Schilling et al, 2019;Lass-Hennemann et al, 2020;Civilotti et al, 2021;Juczynski and Oginska-Bulik, 2021;Oginska-Bulik and Juczynski, 2021;Righi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%